Sistem Pengaturan Pendingin Ruangan dengan Menggunakan Thermoelectric dan Blower Motor Direct Current - Zul Fakhri; Ahmad Daelami; Bayudin; Atik Charisma (Fakultas Teknik - Universitas Jenderal Achmad Yani, 2022)
The increase in temperature affects the comfort of the dwelling, especially the bedroom area, so it requires a room conditioning tool so that the temperature remains stable and comfortable. Air conditioning tools that are commonly used by the public are now using less environmentally friendly substances because they can damage the ozone layer and are expensive to operate and maintain. Cooling and air conditioning technology is becoming very important at this time. Various technologies are already on the market to meet people's needs. This research describes the design and realization of an air conditioning control system using a thermoelectric and direct current blower motor. This system consists of a Peltier, a DS18B20 temperature sensor and a DC blower motor using PID control. In the test the blower temperature without peltier is measured with an average temperature of 25,650C while with peltier it is 22,270C. The most optimal PID parameters using the trial and error method are Kp = 20, Ki = 2, and Kd = 20 with a set point of 170C.